Association between neighborhood environment and self-reported and objectively measured physical activity in Hispanic families - Rebecca Nissen; Rebecca Nissen; Kiria Fraga; Alexander Woll; Sonia Vega-López; Janina Krell-Roesch; Noe C. Crespo (Frontiers in Sports and Active Living)
ObjectiveGiven the limited information about how neighborhood environment relates to physical activity (PA) in Hispanic families, this work examined cross-sectional associations between perceived neighborhood environment and PA of Hispanic parents and children.MethodsParticipants were 137 Hispanic parent-child dyads (children aged 6–11 years) in South Phoenix, AZ, USA. Parents completed a survey about their own and their child's PA, and perceptions of neighborhood environment (i.e., scores of walking/cycling, neighborhood aesthetics, traffic safety, and crime rate) using NEWS survey. Participants also wore an accelerometer for 7 days.ResultsChildren engaged in 60 min of moderate-to-vigorous PA (MVPA) on 2.3, and parents in 30 min of MVPA on 2.1 days per weeks. Additionally, children engaged in 104.4 min, and parents in 65.3 min of accelerometer-assessed MVPA per day. Participants rated their neighborhood (range 0–4) as favorable regarding walking/cycling (mean score 3.1), aesthetics (2.4), traffic safety (2.5), and crime rate (3.1). In Spearman correlation analyses, better neighborhood aesthetics was associated with higher accelerometer-assessed MVPA in children (r = 0.25, p = 0.04). Multiple linear regression analyses revealed an association between traffic safety and parent-reported MVPA in children (standardized beta coefficient 0.19, p = 0.03). No further associations between scores of neighborhood environment and physical activity in either children or parents were observed.ConclusionOur findings may underscore the importance of neighborhood aesthetics and traffic safety for PA engagement in children. Longitudinal studies are needed to confirm our observations, and to untangle potential mechanisms linking neighborhood environment and PA in understudied populations such as Hispanics.